Nexus between Household Savings and Gross Capital Formation in Nigeria - Ajagbe, Surajdeen Tunde; Johnson, Adebayo Akanbi; Taoridi, Alaka Adedayo; Gbadebo, Abraham Oketooyin; Aderemi, Timothy Ayomitunde (Acta Universitatis Danubius. Œconomica, 2023)
This study addresses the nexus between household savings and gross capital formation in Nigeria within the periods of 1990 and 2020. After extracting data from the World Development Indicators, the data were analyzed within the techniques of Fully Modified Least Squares and Granger causality. Consequently, the following conclusion among others are drawn from this study. First and foremost, household savings and gross capital formation have a positive and significant relationship in Nigeria. But, total credit to private sector and capital formation have a significant inverse relationship. FDI, broad money supply and interest rate have an insignificant direct relationship with capital formation. But, the case of exchange rate shows an insignificant inverse relationship with capital formation. Similarly, capital formation and household savings have a uni-directional causality, which flows from capital formation. Also, gross capital formation Granger causes interest rate and total credit to private sector. Therefore, this study submits that household savings contributes both positive and significant influence on gross capital formation in Nigeria in one hand, and gross capital formation is a strategic factor that propels household savings in Nigeria on the other hand. In the light of the above findings, this study recommends that the Nigerian policymakers should embark on a favourable monetary policy that will spur broad money supply, interest rate, exchange rate and credit to private sector in the direction of capital accumulation. In the same page, the policy that will promote saving attitude of the Nigerians should be embarked on the economy will enjoy a sustainable capital accumulation.